Perceived usefulness of agricultural information sought on-line and broadcast in rural Mozambique: a case study of two Community Multimedia Centres (CMCs) - Fuel, Isaias Carlos (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2013)
The wealth of information available on the Internet holds the potential to aid development in Africa. In order to be effective, such information needs to be contextualised to respond to local needs and practices. The combination of old and new media can support uptake and improve acceptance of new technologies in developing countries. The purpose of this qualitative study was to investigate the perceived usefulness of agricultural information sought on-line and broadcast via community radio in the two Community Multimedia Centres (CMCs) of Namaacha and Murrombene, in rural Mozambique. The data was generated from focus group discussion, individual interview, document analysis, and observation involving farmers and radio presenters. The study has shown that on-line agricultural information responds to the needs of the farmers because it contributes to eliminate pests and help farmers to make decisions about their activities. The study has also shown that there is a communication gap between farmers, extension workers, and volunteer reporters working at the community radios of the two CMCs. Volunteers have no agricultural knowledge. The problem this creates manifests itself primarily when they try to translate on-line agricultural information from Portuguese into local languages. Farmers have difficulties expressing their problems. Extension workers are not available to act as experts and mediators between volunteers and farmers. A collaborative website focusing on locally relevant content was suggested as a possible improvement.
Keywords: Radio in community development -- Mozambique; Radio broadcasting -- Mozambique; Radio stations -- Mozambique; Digital media -- Mozambique; Rural development -- Mozambique; Agriculture -- Mozambique